Predictors of Mortality in Progressive Fibrosing Interstitial Lung Diseases - Chen, Xianqiu; Guo, Jian; Yu, Dong; Jie, Bing; Zhou, Ying (Frontiers in Pharmacology, 2021)
Background: Progressive fibrosing interstitial lung disease (PF-ILD) and idiopathic pulmonary fibrosis (IPF) share similar progression phenotypes but have different pathophysiological mechanisms. The purpose of this study was to assess the clinical characteristics and outcomes of patients with PF-ILD in a single-centre cohort. Methods: Patients with PF-ILD treated in Shanghai Pulmonary Hospital from Jan. 2013 to Dec. 2014 were retrospectively analysed. Baseline characteristics and clinical outcomes were collected for survival analysis to identify clinical predictors of mortality. Results: Among 608 patients with ILD, 132 patients met the diagnostic criteria for PF-ILD. In this single-centre cohort, 51 (38.6%) patients had connective tissue disease-associated interstitial lung disease (CTD-ILD), and 45 (34.1%) had unclassifiable ILDs. During follow-up, 83 patients (62.9%) either died (N=79, 59.8%) or underwent lung transplantation (N=4, 3.0%) with a median follow-up time of 53.7 months. Kaplan-Meier survival curves revealed that the 1-, 3- and 5-year survival rates of PF-ILD were 90.9%, 58.8% and 48.1%, respectively. In addition, the prognosis of patients with PF-ILD was similar to that of patients with IPF, while it was worse than that of non-PF-ILD patients. Multivariate Cox regression analysis demonstrated that high-resolution computed tomography (HRCT) score (HR 1.684, 95% CI 1.017–2.788, P=0.043) and systolic pulmonary artery pressure (SPAP) >36.5 mmHg (HR 3.619, 95% CI 1.170–11.194, P=0.026) were independent risk factors for mortality of PF-ILD. Conclusion: The extent of fibrotic changes on HRCT and pulmonary hypertension were predictors of mortality in patients with PF-ILD.